The Effect of Voluntary Physical Activity in an Enriched Environment and Combined Exercise Training on the Satellite Cell Pool in Developing Rats - Rostami, Samira; Salehizadeh, Reyhaneh; Shamloo, Sahar; Fayazmilani, Rana (Frontiers in Physiology, 2022)
Aim: Postnatal skeletal muscle growth is strongly associated with a satellite cell pool. Early adolescence might be a crucial period when different exercise training interventions have specific consequence on satellite cells. Pax7 and MyoD have been suggested as the leading indicators of satellite cell activation. Methods: In this study, pre-adolescent male rats (n = 18) were either subjected to an enriched environment that facilitated physical activities or combined training or control for three weeks. The flexor hallucis longus muscle was removed for biochemical and histochemical analysis. Results: Findings demonstrated that exercise trained rats displayed high levels of serum IGF-1 (p <0.05). There was an increase in Pax7 (p <0.05) and MyoD (p <0.001) mRNA expression. A significant increase in the mean fiber area (p <0.01), satellite cell (p <0.001), and myonuclear numbers (p <0.01) were also observed in both intervention groups. Importantly, enriched rats showed lower corticosterone levels (p <0.05) compared to training ones. Regarding performance, trained and enriched rats had significant improvement in forelimb grip strength (p <0.01) and load-carrying capacity (p <0.05). Conclusion: Type of physical exercise is an essential part in changing satellite cells pool. Different and frequent physical activities in an enriched environment can be effective for muscle development.